Socratic questioning: a philosophical approach to develop critical thinking skills. - Abdullah, Norillah (2022)
Thinking critically entails rationality principles, which is seen as an essential ability that must be polished by everyone to acquire and use the ability in daily lives. Evidently the Greek philosopher Socrates set the agenda for critical thinking. He believed no idea can be taught directly, and helped his students reach a deep level of understanding and thinking by questioning the underlying beliefs and assumptions. Learning to think is a vital skill that needs to be taught from an early stage to solve problems and make decisions effectively. Henceforth, Socratic questioning is one of the approaches used by educators in schools and universities to produce intelligent thoughts and give new recommendations to address incumbent issues that are related to philosophical and critical thinking skills. Therefore, this paper attempts to highlight the Socratic questioning as a philosophical approach to develop critical thinking among students. The paper further accentuates the conceptual clarification; the Socratic questioning approach; the strength of Socratic questioning; the role of Socratic questioning in developing critical thinking skills and the limitation of Socratic questioning. Finally, the paper emphasises that teaching Socratic questioning provides students with an excellent atmosphere of satisfying one’s curiosity and a compliment that leads to the solution of philosophical problems determined by critical thinking skills.